The effects of organisational innovation and creativity on human resources practices in the ministry of interior UAE - Althehli, Fatima Ali Rashed Naser (2024)
Well-managed businesses traditionally view creativity and innovation as a path to success. Creativity stimulation and the exploration of wholly new and uncharted territory result in a rise in the organisation's production. The key to cost-effective company solutions is encouraging people to think creatively and providing them with the resources and time to explore new areas for innovative ideas. Creativity enhances the problem-solving process. Creativity is essential for organisations today, especially given the market's dependence on cutting-edge technologies. The combination of creative minds has the potential to bring innovative company concepts to fruition. This study aimed to assess the effects of innovation and creativity on human resources practices in the Interior Ministry of the UAE. This study employs a quantitative approach by using a questionnaire as an instrument for data collection. In the data collection, 300 employees from the Ministry of Interior based in Abu Dhabi were chosen as the respondents. SPSS and PLS-SEM software were used for the data analysis. The findings show that there is an insignificant causal relationship between administrative innovation and human resources practices, while process innovation has a significant causal relationship with human resources practices, with a path coefficient of 0.229, a t-statistic of 2.166, and a p-value of 0.031. Cumulatively, about 45.1 percent of the variance in human resources practices in the UAE is explained by administrative innovation, process innovation, government services, motivation, communication, and technology creativity, as indicated by the coefficient of determination (R2) value of 0.451. To attain successful human resources practices in the United Arab Emirates, the research suggests devoting special attention to innovation and creativity in the ministry since they affect human resources practices. There is a need to enhance process innovation by implementing systems that can accept process modifications and execution, hence encouraging a methodical search for new product ideas. The use of additional technology-based innovations to create human resources practices is vital, especially in the management of departmental data demands, the use of technology to speed up the decision-making process, and the utilisation of technology tools in data collection and usage.